2019
DOI: 10.1177/1470320319870945
|View full text |Cite
|
Sign up to set email alerts
|

ACE insertion/deletion genetic polymorphism, serum ACE levels and high dietary salt intake influence the risk of obesity development among the Saudi adult population

Abstract: Introduction: Angiotensin-converting enzyme ( ACE), which contributes to adipocyte growth, differentiation and function, has recently been linked with both salt metabolism and obesity development. Therefore, this study has aimed to investigate the putative relationship between ACE genetic polymorphism, serum ACE levels and salt consumption on the risk of developing obesity in the Saudi population. Materials and methods: ACE genotype status of 267 adult Saudi volunteers (124 obese and 143 non-obese) was correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
8
0
4
Order By: Relevance
“…Occurrence of ACE2 rs1514283 T/C, rs4646155 C/T, rs4646176 C/G, rs879922 G/C, rs2074192 C/T, rs2106809 C/T, rs4240157 C/T, rs4646155 C/T, rs4646188 C/T, rs4830542 C/T, rs879922 C/G polymorphisms were reported in healthy population of China [ 60 ]. Incidence of ACE2 rs2106809 I/D polymorphism was reported in healthy individuals of India and Saudi Arabia [ 61 , 62 ]. Genotype frequency of ACE2 rs1800764-3903C/T, rs4459609-5486A/C, rs4459609-3678Ins/Del, and rs274601-638A/G polymorphisms were reported in general population of Poland [ 63 ] ( Table −1 ).…”
Section: Ace2 Polymorphism In General Populationmentioning
confidence: 99%
“…Occurrence of ACE2 rs1514283 T/C, rs4646155 C/T, rs4646176 C/G, rs879922 G/C, rs2074192 C/T, rs2106809 C/T, rs4240157 C/T, rs4646155 C/T, rs4646188 C/T, rs4830542 C/T, rs879922 C/G polymorphisms were reported in healthy population of China [ 60 ]. Incidence of ACE2 rs2106809 I/D polymorphism was reported in healthy individuals of India and Saudi Arabia [ 61 , 62 ]. Genotype frequency of ACE2 rs1800764-3903C/T, rs4459609-5486A/C, rs4459609-3678Ins/Del, and rs274601-638A/G polymorphisms were reported in general population of Poland [ 63 ] ( Table −1 ).…”
Section: Ace2 Polymorphism In General Populationmentioning
confidence: 99%
“…The ACE2 polymorphism has been associated with varying degree of disease severity and clinical outcomes of COVID-19, with absence of ACE D/D genotype conferring protection against severe lung injury [33]. The African Americans with high frequency of D allele have depicted higher mortality rates in USA [34,35]. Similarly, higher fatalities have been reported from many parts of Europe (https://ec.europa.eu/eurostat/statistics-explained/index.php/Main_Page, accessed on 12 October 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, endurance sports are characterized by a relatively low-moderate intensity and longduration events, where oxidative metabolism is the predominant source for ATP resynthesis during exercise (Petro & Bonilla, 2015). The insertion of the 287 base-pair Alu sequence in the ACE gene has been associated to slow-twitch type I muscle fibres (Papadimitriou et al, 2016), and is reported to account for the ≈47% of fluctuations in the protein activity in plasma (Sabir et al, 2019;Woods et al, 2001). The insertion of this sequence has been related to less vasoconstriction due to a decrease in the ACE serum levels and activity and, therefore, higher oxygen availability and nutrients delivery for muscle fibres in contraction (Gunel et al, 2014).…”
Section: Discussionmentioning
confidence: 99%